The Effect of Educational Intervention Based on the Theory of Planned Behavior on the Promotion of Nutritional Behaviors of Pregnant Mothers - Fariba Etezadi; Alireza Ghaemi; Zahra Jalili (Mazandaran University of Medical Sciences, 2019)
Introduction and purpose: Proper nutrition during pregnancy is of utmost importance in the maintenance of maternal and fetal health. This study aimed to determine the effect of educational intervention based on the theory of planned behavior in the promotion and  nutritional behaviors of pregnant women referring to comprehensive health centers in Amol, Iran in 1397. Methods: This semi-experimental interventional research was performed on 72 pregnant women in the first trimester of pregnancy who were randomly assigned to intervention and control groups. The instrument utilized in this study was a questionnaire developed by the researcher and used after the validity and reliability confirmation. The P-value <0.05 was considered statistically significant. Results: The results showed that there was a significant difference between the mean scores of knowledge, attitude, abstract norm, perceived behavior control, behavioral intention, and the behavior of the experimental group after the intervention in educational intervention group (P <0.001). Conclusion: Based on the results of this study, educational intervention based on planned behavioral theory was effective in the promotion of nutritional behaviors of pregnant women. Educational intervention of this theory could be a appropriate theoretical framework for the design and implementation of interventions to promote nutritional behavior of pregnant women.